BIOCHEMICAL FACTORS AFFECTING THE FREQUENCY OF SEIZURES IN EPILEPTIC PATIENTS AFTER COVID-19 INFECTION - Khanifa Khalimova; Nilufar Rashidova; Saykha Ilkhomova (Central Asian Journal of Medicine, 2025)
The COVID-19 pandemic has significantly affected various health conditions, including epilepsy, with long-term implications. This study explores the biochemical factors influencing the frequency of seizures in epileptic patients following COVID-19 infection. Biochemical markers such as inflammation markers (CRP, IL-6), hypoxia and thrombosis markers (D-dimer), metabolic indicators (glucose, insulin, HbA1c), and electrolyte imbalances (Na+, K+, Ca2+, Mg2+) were assessed. The results show that COVID-19 infection increased seizure frequency, with heightened levels of inflammation, thrombosis, and metabolic disturbances contributing to this change. Understanding these biochemical factors can help develop targeted therapeutic strategies for managing seizures in epileptic patients post-COVID-19.